2015
DOI: 10.1061/(asce)st.1943-541x.0001105
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Shear-Out Capacities of Structural-Steel Bolted Connections

Abstract: Based on the previous research results of the authors, this paper presents an accurate and consistent equation for determining the ultimate shear-out capacity of a structural steel bolted connection. The equation is verified against independent laboratory test results obtained by other researchers around the world. Comparisons against alternative equations found in the design specifications and literature are also included. The paper explains why certain equations appear to be accurate for particular configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…However, these equations differ not only in coefficients but also in variables, and always overestimate or underestimate the shear-out capacity of the bolted connection. Teh and Uz (2015) have shown that the shear-out capacity given by the North American cold-formed steel specification is too conservative for hot-rolled steel bolted connections, but it is uncertain whether the same outcome applies to cold-reduced sheet steel connections as the latter often have reduced material ductility. To the authors' knowledge, the European and Australian shear-out provisions have never been checked against cold-reduced sheet steel connections since they were adopted from the respective provisions for hot-rolled steel connections.…”
Section: Problem Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these equations differ not only in coefficients but also in variables, and always overestimate or underestimate the shear-out capacity of the bolted connection. Teh and Uz (2015) have shown that the shear-out capacity given by the North American cold-formed steel specification is too conservative for hot-rolled steel bolted connections, but it is uncertain whether the same outcome applies to cold-reduced sheet steel connections as the latter often have reduced material ductility. To the authors' knowledge, the European and Australian shear-out provisions have never been checked against cold-reduced sheet steel connections since they were adopted from the respective provisions for hot-rolled steel connections.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Equation 8has been demonstrated by Teh and Uz (2015) to be accurate for hotrolled steel specimens tested by independent researchers. The use of the effective shear planes depicted in Figure 2.2 has also been comprehensively validated by Elliott et al (2019) through finite element analysis incorporating shear fracture simulation.…”
Section: Proposed Shear-out Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The shear-out data 251 encompass those presented by Teh & Uz (2015a), while the rest can be found in Tables 2 and 252 3. It can be seen that the authors' equations are significantly more consistent and more 253 accurate than the current AISC equations (AISC 2010(AISC , 2015.…”
mentioning
confidence: 99%